Polysemy of Coloronyms “White” and “Black” in Proverbs and Sayings of the Russian and German Languages - N. A. Krupnova (Дискурс профессиональной коммуникации, 2025)
Given the growth of intercultural professional communication, a profound understanding of culture-specific connotations embedded in language, particularly in paremiological units that encapsulate folk wisdom and cultural attitudes, becomes crucial. Misinterpretation of such units, especially those involving color symbolism, can lead to significant communicative breakdowns in professional situations. This study investigates the polysemy of the coloratives “white” and “black” in Russian and German proverbs and sayings, highlighting its scientific novelty in its comparative aspect and in identifying potential areas of divergence in cultural perception. The aim is to determine and compare the meanings of these color lexemes at semantic and morphological levels. The empirical material comprises proverbs and sayings selected through continuous sampling from internet resources and lexicographical sources. Methods employed include semantic analysis, interpretation via synonym selection, grammatical analysis, and comparative analysis. The findings establish that the coloratives “white” and “black” are highly polysemous in the paremiological funds of both languages, constituting a total of 33 lexical-semantic variants (LSVs). Of these, only 7 LSVs show complete or partial coincidence (e.g., “white” as a synonym for the best, pleasant, light; or signifying distinctiveness). Conversely, 26 LSVs are unique to one language, reflecting ethnocultural specificity. For instance, Russian proverbs attribute meanings to “white” such as ‘difficult, overwhelming,’ ‘beautiful,’ or ‘outwardly beautiful but inwardly bad,’ which are not characteristic of German paremias. Morphologically, these coloratives are most frequently expressed as adjectives. The results, detailing convergences and divergences in the semantics of these color terms across the two linguacultures, hold direct relevance for professional communication. Understanding these differences is vital for preventing intercultural misunderstandings, enhancing the effectiveness of business negotiations, stimulating successful international collaborations, and optimizing foreign language training for professionals engaged in intercultural interaction.